2019
DOI: 10.1038/s41586-019-1451-5
|View full text |Cite|
|
Sign up to set email alerts
|

Human placenta has no microbiome but can contain potential pathogens

Abstract: We sought to determine whether preeclampsia, delivery of a small for gestational age infant or spontaneous preterm birth were associated with the presence of bacterial DNA in the human placenta. Here we show that there was no evidence for the presence of bacteria in the large majority of placental samples, from both complicated and uncomplicated pregnancies. Almost all signals were related either to acquisition of bacteria during labour and delivery or contamination of laboratory reagents with bacterial DNA. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
520
3
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 556 publications
(559 citation statements)
references
References 35 publications
(42 reference statements)
17
520
3
5
Order By: Relevance
“…This may impact our results in several ways. None of these studies were executed with quality control measures that can affect estimates of microbial diversity, such as process blanks during DNA extraction, no template controls during PCR, and batch effects during library preparation [48][49][50][51]. While we applied an arbitrary cutoff to remove contaminants, it is difficult to know how potential contaminants may affect the observed results.…”
Section: Discussionmentioning
confidence: 99%
“…This may impact our results in several ways. None of these studies were executed with quality control measures that can affect estimates of microbial diversity, such as process blanks during DNA extraction, no template controls during PCR, and batch effects during library preparation [48][49][50][51]. While we applied an arbitrary cutoff to remove contaminants, it is difficult to know how potential contaminants may affect the observed results.…”
Section: Discussionmentioning
confidence: 99%
“…The healthy neonate is born sterile. Recent reports suggesting the presence of a microbiota in healthy placental and fetal tissue before birth have been challenged and most probably reflect the detection of free bacterial nucleic acid molecules derived from environmental sources . Nevertheless, the fetal tissue is of course not completely shielded from microbial constituents and innate immune signals.…”
Section: Development Of the Neonatal Microbiotamentioning
confidence: 99%
“…Recent reports suggesting the presence of a microbiota in healthy placental and fetal tissue before birth have been challenged and most probably reflect the detection of free bacterial nucleic acid molecules derived from environmental sources. 8,9 Nevertheless, the fetal tissue is of course not completely shielded from microbial constituents and innate immune signals. A recent study in mice reported on the priming effect of aryl hydrocarbon receptor ligands of the maternal microbiota on the offspring's immune system with elevated numbers of type 3 innate lymphoid and myeloid cells known to participate in the antibacterial host response.…”
Section: Development Of the Neonatal Microbiotamentioning
confidence: 99%
“…7_1_47FAA (Figure 6D, Table S3). We observed a lower relative abundance of Ureaplasma parvum in individuals who delivered by cesarean section (Figure 6E, Table S3), a bacterium commonly isolated from pregnant women (Anderson et al, 2013) and recently reported in the lower respiratory tract of preterm infants (Pattaroni et al, 2018) and in preterm placenta (de Goffau et al, 2019). Compared with vaginal deliveries, the plasma concentrations of testosterone, androstenedione, methionine, threonine and tryptophan were significantly lower in women who experienced caesarean section (Figure 6D, 6E).…”
Section: Resultsmentioning
confidence: 52%
“…Individuals dominated by B. breve had older age at vaginal sexual debut compared to those dominated by L. cripspatus or L. iners (Figure 2B, p = 0.00026 and p = 0.0019, respectively). Streptococcus agalactiae (Group B Streptococcus ), a bacterium responsible for neonatal sepsis and recently reported in placenta (de Goffau et al, 2019), could be detected in 5.62 % of the individuals (Figure 2A, Table S1C). Other microorganisms including Prevotella bivia , Escherichia coli , Ureaplasma parvum , human papillomavirus (HPV), herpesviruses, Influenza A virus and Haemophilus influenzae were abundant in some individuals (Figure 2A, Table S1C).…”
Section: Resultsmentioning
confidence: 86%